The Effect of Sleep Duration on Overweight or Obesity in Female Adolescents: A Meta-Analysis Study - Jannah, Putri Isriyatil; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Overweight or obesity is a condition of excessive accumulation of fat in the body which is indicated by a Body Mass Index value exceeding 25 kg/m2. WHO estimated that in 2022 adolescents will experience more obesity cases than underweight cases. One of the behaviors that can reduce the risk of overweight and obesity is having adequate sleep duration. This study aimed to analyze the magnitude of the effect of sleep duration on overweight or obesity in female adolescents with a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis study. The study was carried out by following the PRISMA diagram. The process of the search for articles through a database that included: PubMed, Google Scholar, and Springer Link. The articles were selected in the period 2009-2020. The keywords used include: